Features of the Development of Social Activeness of Lithuanian Teacher - Poškus, Kazys (Acta Paedagogica Vilnensia, 1991)
The social activeness of a teacher is defined as a personal quality and as an integral quality of a member of the society, includes many features – the ideational, public spirit, humanity, national identity, creativity, etc., and is realized in the social, political, cultural, professional and other spheres. This article aims to expose the manifestations of the social activeness of teachers under various historical circumstances. It discusses the teachers' resistance polonization and Russian tsar repressions of 19th and the beginning of the 20th centuries. It describes the activities of the teachers of secret Lithuanian schools. Teachers remained among the most active members of the public in independent Lithuania (1918-1940). During the first Soviet occupation (1940-1941) a number of teachers have been identified as “malicious” and politically unreliable. They were deported, or discharged. Repressions continued during the post-war years. Over time the social activity of the majority of teachers has notably diminished. Some teachers have become a tool of dissemination of Soviet ideology.
Keywords: teacher; social activeness; history of pedagogy